PENILAIAN DAUR HIDUP PRODUK KOPI ROBUSTA ORGANIK PADA AGROINDUSTRI KOPI KLUNGKUNG - Elida Novita; Dini Retno Widyaningsih; Hendra Andiananta Pradana (AGROINTEK, 2023)
Organic robusta coffee cultivation in Klungkung Village can cause environmental pollution and has the potential to produce greenhouse gases (GHG) due to inefficient use of energy. Upstream processes or gardens use organic fertilizers without proper knowledge. Meanwhile, downstream or processing uses technology and produces waste that is not yet environmentally friendly. This study aims to determine how much impact the processing of organic robusta coffee can make, so that the product can be said to be feasible as an environmentally friendly product. The method used in this research is Life Cycle Assessment (LCA) which has stages of determining goals and scope, life cycle inventory, life cycle impact assessment and interpretation. Processing of organic robusta coffee products produces a GWP of 21,2768 kg CO2-eq and the efficiency of energy use shows a NER value of 0.02 and a NEV of -153.94. The recommended alternative improvement is the use of coffee horn skin which is processed into briquettes as a substitute for LPG fuel in the roasting process. If the alternative recommendations are implemented, it can reduce the GWP value to 20.4374 kg CO2-eq and increase energy use efficiency to a NER value of 1.09 and NEV of 9.86. The environmental impact resulting from this research is the amount of greenhouse gases (GHG) resulting from the organic robusta coffee production process, if not repaired, it will pollute the surrounding environment.